Clinic of Acute Rheumatic Fever in Children Transmission Characteristics (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
In this articleCorrect information is given about the specifics of the clinical course of acute rheumatic fever in young children. Acute rheumatic fever (rheumatism) is a systemic inflammatory disease of the connective tissue, accompanied by damage to the cardiovascular system.